Educational support to improve female entrepreneurship: A case study amidst social inequalities - Rodrigues, Graziela Perretto; Ciscato , Cleia Denise Santos (REGEPE Entrepreneurship and Small Business Journal, 2025)
Objective of the study: This study investigates how higher education can mitigate social inequalities by integrating academic content with female micro-entrepreneurship, addressing socioeconomic challenges through strategic business planning. It specifically investigates the application of active learning methodologies and business tools to enhance the sustainability and resilience of female-led microenterprises. Methodology/Approach: A qualitative case study approach was employed, focusing on a female micro-entrepreneur in Curitiba, Brazil, who participated in a university extension project. The study applied Problem-Based Learning (PBL) and Business Model Canvas (BMC) to provide strategic planning support. Data collection included semi-structured interviews, direct observations, and document analysis to ensure a comprehensive understanding of the case. Main Results: The findings reveal that structured educational support led to significant improvements in business organization, financial planning, and market positioning. The entrepreneur developed a more robust business model, increasing operational efficiency and strategic decision-making capabilities. Additionally, the research highlights the role of active learning methodologies in fostering entrepreneurial skills and addressing gender disparities in business. Relevance/Originality: This study contributes to the literature by demonstrating how academic-business collaboration through extension activities strengthens entrepreneurial capacity among women. It also provides empirical evidence on the effectiveness of integrating PBL and BMC in supporting female micro-entrepreneurs, an area with limited previous exploration. Social/Management Contributions: The study reinforces the potential of female micro-entrepreneurship when supported by structured strategic planning and educational collaboration. It underscores the importance of inclusive entrepreneurship policies and university-led initiatives in reducing gender-based economic disparities.